Expansion of the brown shrimp Crangon crangon L. onto juvenile plaice Pleuronectes platessa L. nursery habitat in the Westfjords of Iceland - Koberstein, Marla J., 1983- (2013)
Sandy-bottom coastal ecosystems provide integral nursery habitat for juvenile fishes, and threats to these regions compromise populations at this critical life stage. The threat of aquatic invasive species in particular can be difficult to detect, and climate change may facilitate the spread and establishment of new species. In 2003, the European brown shrimp Crangon crangon L. was discovered off the southwest coast of Iceland. This species is a concern for Iceland due to the combination of its dominance in coastal communities and level of predation on juvenile flatfish, namely plaice Pleuronectes platessa L., observed in its native range. The purpose of this study was to 1) determine the expansion of the brown shrimp in the Westfjords and map its relative density and 2) determine the role the Westfjords plays in providing essential nursery habitat to juvenile Icelandic plaice, a commercial fishery in Iceland that has experienced a decline in landings in recent years. Research goals were achieved by collecting juvenile plaice and brown shrimp using a beam trawl at eleven sampling stations between July 24 and July 31, 2012. Results indicate a northward expansion of the brown shrimp as far as Bolungarvík. The highest density (26.67 ind. per 100m2), was found at Brjánslækur. Multiple generations of the brown shrimp were also observed, indicating reproducing populations. High densities (greater than 200 ind. per 100m2) of 0-group plaice were also found at three sites. These two findings offer a preliminary assessment of the potential risk the brown shrimp may pose to 0-group plaice, and establish the need for continued monitoring of the brown shrimp at these stations. Further, this study has identified essential juvenile plaice habitat in the Westfjords for the success of the Icelandic plaice fishery. Sandfjörur gegna mikilvægu hlutverki sem uppeldisslóðir fyrir ungviði fiska. Öll röskun á slíkum svæðum er líkleg til að skaða stofnana á viðkvæmum lífsstigum. Erfitt er að greina áhrif af ágengum tegundum í sjó en ...